2023
DOI: 10.1029/2022je007513
|View full text |Cite
|
Sign up to set email alerts
|

Can Clay Mimic the High Reflectivity of Briny Water Below the Martian SPLD?

Abstract: It has recently been suggested that clay minerals, which are widespread on the Martian surface, could be the possible source of the basal bright reflections detected by MARSIS at Ultimi Scopuli, instead of briny water. This hypothesis is based on dielectric measurements on a wet Ca‐Montorillonite (STx‐1b) sample conducted at 230 K, which reported permittivity values (apparent permittivity of 39 at 4 MHz) compatible with the median value of 33 retrieved by MARSIS 4 MHz data inversion in the high reflectivity ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…They found that even in clay samples with high moisture content, the apparent permittivity exhibited was only 8.4 at 4 MHz and 230 K, and it was only 4.1 at 200 K. These values were significantly lower than the actual inversed values. This research has conclusively demonstrated that materials such as clays cannot produce the strong reflections observed by MARSIS [33].…”
Section: Other Possibilities Causing the Bright Reflectionmentioning
confidence: 65%
See 2 more Smart Citations
“…They found that even in clay samples with high moisture content, the apparent permittivity exhibited was only 8.4 at 4 MHz and 230 K, and it was only 4.1 at 200 K. These values were significantly lower than the actual inversed values. This research has conclusively demonstrated that materials such as clays cannot produce the strong reflections observed by MARSIS [33].…”
Section: Other Possibilities Causing the Bright Reflectionmentioning
confidence: 65%
“…In response to these doubts, researchers have conducted laboratory experiments to measure the dielectric properties of relevant materials under corresponding conditions. They argue that materials such as clay cannot cause such bright reflections and they continue to support the view that the cause of the bright reflections is brines with high chloride content [32,33]. Currently, the cause of these bright reflections remains inconclusive.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Layered interference within the SPLDs and high-density igneous material with metallic inclusions are also thought to cause (Lalich et al [117], Grima et al [118]). Laboratory experiments have been conducted to measure the dielectric properties of relevant materials under similar conditions, and materials like clay cannot produce such bright reflections (Mattei et al [119], Cosciotti et al [120]).…”
Section: Radar Observationmentioning
confidence: 99%
“…Because of its significance in the study of the biologic potential of Mars, the identification of liquid water has been closely scrutinized by the scientific community at large, and several counterarguments and alternative interpretations of the MARSIS measurements have been proposed over the last four years. Although the debate has yet to reach a conclusion, geologic evidence, all experimental work, and most electromagnetic modeling favor the presence of brines, possibly as interstitial fluid in sediments [160][161][162][163][164][165][166][167]. Dense measurement coverage in the polar regions has enabled 3-dimensional processing of the sounding data to improve resolution and better map continuous structures in the ice caps [168,169].…”
Section: Marsmentioning
confidence: 99%